Genotyping of circulating cell‐free DNA enables noninvasive tumor detection in myxoid liposarcomas. Issue 4 (9th March 2019) - Braig, David; Becherer, Caroline; Bickert, Christiane; Braig, Moritz; Claus, Rainer; Eisenhardt, Anja E.; Heinz, Juergen; Scholber, Jutta; Herget, Georg W.; Bronsert, Peter; Fricke, Alba; Follo, Marie; et al.
Abstract : Soft tissue sarcomas (STS) are rare tumors of mesenchymal origin. About 50% of patients with STS experience relapse and more than 30% will die within 10 years after diagnosis. In this study we investigated circulating free DNA (cfDNA) and tumor‐specific genetic alterations therein (circulating tumor DNA, ctDNA) as diagnostic biomarkers. Plasma concentrations and fragmentation of cfDNA was analyzed with quantitative PCR. Patients with STS ( n = 64) had significantly higher plasma concentrations and increased fragmentation of cfDNA when compared to patients in complete remission ( n = 19) and healthy controls ( n = 41) ( p < 0.01 and p < 0.001). Due to overlapping values between patients with STS and controls, the sensitivity and specificity of these assays is limited. Sensitive assays to detect genomic alterations in cfDNA of synovial sarcomas (t(X;18)), myxoid liposarcomas (t(12;16) and TERT C228T promoter mutation) and well‐differentiated/de‐differentiated liposarcomas (MDM2 amplifications) were established. ctDNA was quantified in nine liposarcoma patients during the course of their treatment. Levels of breakpoint t(12;16) and TERT C228T ctDNA correlated with the clinical course and tumor burden in patients with myxoid liposarcomas ( n = 4). ctDNA could detect minimal residual disease and tumor recurrence. In contrast, detection of MDM2 amplifications was not sensitive enough to detect tumors in patients with well‐differentiated/de‐differentiated liposarcomas ( n = 5). Genotyping of cfDNA for tumor specific genetic alterations is a feasible and promising approach for monitoring tumor activity in patients with myxoid liposarcomas. Detection of ctDNA during follow‐up examinations despite negative standard imaging studies might warrant more sensitive imaging (e.g. PET‐CT) or closer follow‐up intervals to timely localize and treat recurrences. Abstract : What's new? Detection of recurrence in patients with myxoid liposarcomas is difficult and costly, as metastatic disease occurs throughout the body. Circulating DNA analysis holds the potential to improve and simplify cancer detection and treatment prediction, but to date it has mostly been adapted to carcinomas. Here, the authors demonstrate that quantification of circulating tumor‐DNA is also a feasible approach for monitoring tumor activity in patients with myxoid liposarcomas. The novel approach would enable timely, non‐invasive detection of minimal residual disease and tumor recurrence and therefore improve treatment.